2016
DOI: 10.1007/s00402-016-2603-9
|View full text |Cite
|
Sign up to set email alerts
|

The biodegradable spacer as a novel treatment modality for massive rotator cuff tears: a prospective study with 5-year follow-up

Abstract: We conclude that in this initial cohort, arthroscopic implantation of InSpace™ system represented an effective alternative to the existing arthroscopic procedures in patients with painful massive RCT refractory to conservative management. Further randomized controlled trials comparing the clinical and functional outcomes after implantation of the InSpace™ device are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
116
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(123 citation statements)
references
References 30 publications
2
116
0
5
Order By: Relevance
“…This spacer deflates within the first four [ 4 ] months after introduction and fully degrades at ~12 months post implantation, which is the required period for post-operative shoulder rehabilitation. Clinical studies on patients with irreparable RC tears have suggested that the InSpace™ system can clinically reduce pain, enable physiotherapy and restore the range of motion and function in the long-term [ 17 - 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…This spacer deflates within the first four [ 4 ] months after introduction and fully degrades at ~12 months post implantation, which is the required period for post-operative shoulder rehabilitation. Clinical studies on patients with irreparable RC tears have suggested that the InSpace™ system can clinically reduce pain, enable physiotherapy and restore the range of motion and function in the long-term [ 17 - 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since 2012, some authors have reported on the use and results of biodegradable subacromial spacers in the treatment of irreparable rotator cuff tears [90][91][92]. This spacer is located between the acromion and humeral heads; when the deltoid muscle contracts, this spacer assists the humeral head to remain within the glenohumeral joint instead of upward displacement during shoulder forward flexion, abduction, and external rotation.…”
Section: Subacromial Balloon Spacermentioning
confidence: 99%
“…Another had pain at 12 months, and magnetic resonance imaging documented scar tissue that was treated conservatively. Senekovic et al 4,5 had 12 patients follow up at 3 years with continued benefit following arthroscopic ISB placement. This article noted deployment time of 2 to 20 minutes.…”
Section: See Related Article On Page 607mentioning
confidence: 99%